Neutrosophic Bi-ideals in INK algebras (European Journal of Pure and Applied Mathematics, 2025)
The main aim of research article is to identify the Bi-ideals in INK-algebra. This paper provides the proposal to the notion of neutrosophic bi-ideal of INK-algebra and also offers the discussion about the basic operations in particular to order reversing and order preserving property, intersection of two neutrosophic bi-ideals and union of two neutrosophic bi-ideals will be again a neutrosophic bi-ideal by one containing the other. Following to that, there is a discussion between homomorphism and epimorphism of neutrosophic bi-ideals of INK-algebras. Certainly to determine the verification of direct product of two neutrosophic sets in INK-sub algebra is again a neutrosophic sets in INK-sub algebra, and a keen observations regarding the direct product of neutrosophic bi-ideals in INK-algebra.
Keywords: Neutrosophic set-Neutrosophic INK-algebra-Neutrosophic bi-ideal